2016
DOI: 10.1002/pd.4866
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three whole genome amplification methods for detection of genomic aberrations in single cells

Abstract: These data suggest that single cell molecular genotyping and copy number analysis can be accomplished when WGA conditions are optimized. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
0
23
1
Order By: Relevance
“…On the other extreme, TruePrime showed a large ADO rate (> 80%). Still, a 40% ADO rate is much higher than previously reported for Ampli1 25,38,39 . Although values over 40% have been already observed in other experiments for MDA methods 40 GenomiPhi and REPLIg were closer to 60%.…”
Section: Discussioncontrasting
confidence: 63%
“…On the other extreme, TruePrime showed a large ADO rate (> 80%). Still, a 40% ADO rate is much higher than previously reported for Ampli1 25,38,39 . Although values over 40% have been already observed in other experiments for MDA methods 40 GenomiPhi and REPLIg were closer to 60%.…”
Section: Discussioncontrasting
confidence: 63%
“…A previous study has shown that WGA performed on few cultured fetal cells from amniotic fluid did have a sufficient genome coverage to provide accurate detection of major fetal chromosome abnormalities . Some of the authors of this article have previously shown that WGA on single cells could be used to detect copy number changes larger than 1 MB using array CGH …”
Section: Discussionmentioning
confidence: 90%
“…Major chemistries employed in the singlecell WGA include the degenerate oligonucleotide-primed polymerase chain reaction (DOP-PCR), the multiple displacement amplification (MDA), the multiple annealing and looping-based amplification cycles (mALBAC) and the ligationmediated PCR following a site specific DNA digestion as in the case of this study (4,17,19,20,(25)(26)(27). However, besides the operator capability, all these strategies are labor-intensive, require long time of execution and may imply different degrees of errors due to inappropriate starting in the early stages of amplification, or due to the specific chemicals used in the reaction (17,18,28).…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the operator capability, this "pre-amplification" method can imply several technical errors and loss of data as insufficient coverage, allelic dropout, false-positives and false-negatives that definitely affect the analytical quality of the next generation sequencing (NGS) procedure (4,(17)(18)(19)(20).…”
Section: Abstract Background: Isolation and Genotyping Of Circulatinmentioning
confidence: 99%